Three essays on torts - Stapleton, Jane (Oxford : Oxford University Press, 2021)
These essays illustrate the advantages of 'reflexive' tort scholarship by contrasting the reflexive scholarship of judicial analysis with grand theory, then applying reflexive scholarship to the tort of negligence. The final essay presents a wider argument about human responsibility and legal conduct.
This edition also issued in print: 2021.
Includes bibliographical references.
Specialized.
Description based on online resource; title from home page (viewed on January 12, 2021).
Keywords: Torts